Patterns of Commodification of Yoga through Symbolic Narratives in New Media: A Case Study of Instagram Social Media @Deeradewi - Dessy Febrianty (Universitas Medan Area, 2025)
This paper aims to analyze the patterns and forms of commodification of Yoga through the narrative of symbols used on social media as a representation of the characteristics of new media. Similar literature tends to review the commodification of Yoga in conventional media and review Yoga as a lifestyle. However, few studies have analyzed the commodification of Yoga through new media such as interactive, two-way, dispersed social media, even though this phenomenon is increasingly occurring in the digital era. This study uses qualitative methods and content analysis with Jean Baudrillard's theory of Symbolic Capitalism to examine the commodification of Yoga through symbolic narratives on the Instagram account of Deera Dewi, a popular yoga instructor. The study's findings show that the commodification of Yoga is indirectly becoming easier through Instagram social media. This commodification is seen in several forms, such as using exclusive venues as a backdrop for activities, branded yoga equipment, product promotions/sponsorships, collaborations with certain companies, and the participation of individuals from the upper echelons. These four aspects are interrelated, with product promotion and company collaboration being the dominant symbols in the yoga commodification process on the Instagram account. This study shows that the characteristics of new media, such as Instagram, accelerate the commodification of Yoga through symbolic visualization that is exclusive and consumptive.